The Influence of Communication Skills towards Job Performance of The State Civil Apparatus - BIRYANTO, BIRYANTO; HUBEIS, AIDA VITAYALA; MATINDAS, KRISHNARINI; SARMA, MA'MUN (Universitas Muhammadiyah Yogyakarta, 2018)
Communication skills are the basic skills needed by each ASN in performing its job duties. The elements of communication skills that are studied include the skills of speaking, writing, reading, listening, and using media. This study aims to: (1) describes ASN communication skills; (2) analyze the factors that are related and affect the elements of ASN communication skills; and (3) analyze the influence of the elements of communication skills to the achievement of ASN job performance.Â The sample used was 380 respondents, taken using random proportional stratified sample method. This study uses quantitative approach and is strengthened by qualitative through interview result, focus group discussion, and field observation. The results show that ASN communication skills are in sufficient category, with the order of the highest being the skills in using media, listening, speaking, reading, and writing.Â Factors that have a positive and significant effect on all elements of communication skills are individual characteristics of employees and work motivation. Communication skills proved to have a positive and significant impact on ASN job performance, with the strongest predictor being skills in using media.